2023
DOI: 10.3390/foods12050958
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Addition of Hemp Press Cake Flour on the Properties of Bovine and Ovine Yoghurts

Abstract: Hemp press cake flour (HPCF) is a by-product of hemp oil production rich in proteins, carbohydrates, minerals, vitamins, oleochemicals, and phytochemicals. The purpose of this study was to investigate how the addition of HPCF to bovine and ovine plain yoghurts at concentrations of 0%, 2%, 4%, 6%, 8%, and 10% could change the physicochemical, microbiological, and sensory properties of the yoghurts, focusing on the improvement of quality and antioxidant activity, and the issue of food by-products and their utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The water holding capacity (WHC) of the BM-based fermented samples was assessed using the centrifugation method, as per Grasso et al [ 20 ]. The color of the BM-based fermented drink was evaluated using a colorimeter (Konica Minolta, Chroma Meter, CR400, Osaka, Japan), following the methodology outlined by Nakov et al [ 9 ]. Parameters such as L* value (lightness), a* value (red-green intensity), and b* value (yellow-blue intensity) were measured for the BM samples.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The water holding capacity (WHC) of the BM-based fermented samples was assessed using the centrifugation method, as per Grasso et al [ 20 ]. The color of the BM-based fermented drink was evaluated using a colorimeter (Konica Minolta, Chroma Meter, CR400, Osaka, Japan), following the methodology outlined by Nakov et al [ 9 ]. Parameters such as L* value (lightness), a* value (red-green intensity), and b* value (yellow-blue intensity) were measured for the BM samples.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the total polyphenols (TPC) and antioxidant activity of BM-based fermented samples with different BP content, extraction was performed by mixing 10 g of the sample with 30 mL of an 80:20 methanol:water solution on a magnetic stirrer for 30 min. The mixture was then transferred to a centrifuge tube and centrifuged at 8000 rpm at 4 °C for 30 min [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…60 g of protein/100 g, Gul et al [ 3 ] reported app. 37% protein in hazelnut press cake, and Nakov et al [ 4 ] reported 34 g protein/100 g of hemp press cake. Camelina press cake is rich in polyphenols, such as protocatechuic acid, catehin, and p -hydroxybenzoic acid, and contains glucosinolates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%